2007
DOI: 10.1007/s00330-007-0760-5
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous treatment of symptomatic non-parasitic benign liver cysts: Single-session alcohol sclerotherapy versus prolonged catheter drainage with negative pressure

Abstract: To evaluate whether prolonged catheter drainage with negative pressure yields better results than single-session alcohol sclerotherapy in the treatment of symptomatic non-parasitic benign liver cysts. Forty patients were randomly assigned to two groups in a 24-month prospective controlled trial. One group was treated with ultrasound-guided prolonged catheter drainage with negative pressure (20 patients with 24 cysts) and the other group with single-session alcohol sclerotherapy (20 patients with 23 cysts). Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 24 publications
2
35
1
Order By: Relevance
“…The results were similar to several other studies reported in the international literature [28,29]. In practice, we observed that the aspirated cyst fluid was clear at the beginning, but the aspirated liquid became cloudy after the injection of ethanol.…”
Section: Sclerotherapy For Renal Cystssupporting
confidence: 91%
See 1 more Smart Citation
“…The results were similar to several other studies reported in the international literature [28,29]. In practice, we observed that the aspirated cyst fluid was clear at the beginning, but the aspirated liquid became cloudy after the injection of ethanol.…”
Section: Sclerotherapy For Renal Cystssupporting
confidence: 91%
“…There was a significant difference between the success rate of group A (without ethanol concentration monitoring) and group B (with ethanol concentration monitoring). The 100% (21/21) success rate in group B was significantly better compared with other reports [28,29]. There were several factors that might contribute to the high success rate in our group B.…”
Section: Sclerotherapy For Renal Cystscontrasting
confidence: 48%
“…In addition, many centres describe their experience in the management of all cysts and treatments (polycystic and simple, laparoscopic and open). Table 1 summarizes the results following aspiration sclerotherapy of liver cysts 17,20,22,42–53 and Table 2 shows the results following laparoscopic treatment of liver cysts 16,28,30–41,54–59 . While percutaneous sclerotherapy appears to be effective in decreasing cyst size, recurrence rates are higher and data studies reporting experience of both surgical de‐roofing and percutaneous sclerotherapy suggest recurrence rates of 2% versus 75%, respectively 55 .…”
Section: Simple Liver Cystsmentioning
confidence: 99%
“…They contain serous fluid and do not communicate with intrahepatic biliary trees. Simple hepatic cysts are present in 2.5–18% of the general population and are asymptomatic in most cases . However, giant cysts occasionally cause various complications such as abdominal distention, pain, nausea, portal hypertension, and obstructive jaundice .…”
Section: Introductionmentioning
confidence: 99%